Diagnóstico del consumo de energía en un sistema de bombeo para agua en la finca Albán, ubicada en el sector La Esperanza, parroquia Tumbaco, durante el año 2016. Diseño y construcción de un sistema con ariete hidráulico prototipo. - Pineda Pinto, Sixto Orlando (2017)
The provision of water for living beings in many cases requires the implementation of pumping systems for transportation and distribution, which demand energy for their operation. The objective of this research is to evaluate a combined pumping system with hydraulic ram pump in the farm “Alban”, to reduce the consumption of electric energy with the use of water flow; the ram pump uses for its operation mechanical energy, mainly the potential energy of a natural water slope, which is a source of renewable energy. The implementation of this system with water ram pump will reduce the consumption of electric energy compared to a traditional pump system with centrifugal pump. For this research, it was used the Scientific Method, which started with a documentary study that was shown with several experiences of applications, design techniques, and construction of a ram pump to improve agricultural production and livestock in rural areas. In addition to, an experimental work was carried out through a prototype pump system with a ramp pump, which allows a combining of a pump system between a ram pump and a centrifugal pump. Its purpose is to supply a flow of 0,966 m3/h (16,1 l/min) that is required for the production of the Alban’s farm, that is located at 91m height above the water source. The economic evaluation based on the energy savings of the proposal shows that the investment is recoverable in 9 years, considering a current interest rate of 16,06% in the local banks, and is an alternative of social assistance and care environmental.